Coexisting Thyroglossal Duct Cyst with Papillary Thyroid Cancer: A Case Report and Literature Review - Alarfaj, Abdullah A.; Zekri, Ahmed; Alyaeesh, Ibrahim; Alomairin, Ahmed; Al Naim, Abdulrahman (Case Reports in Otolaryngology, 2021)
Thyroglossal duct cysts (TGDCs) are common developmental anomalies in which the thyroglossal duct is not obliterated. Coexisting papillary thyroid cancer and TGDC are uncommon and should be investigated thoroughly to rule out TGDC carcinoma. We report a rare case of coexisting papillary thyroid cancer and TGDC in a 48-year-old man, who presented with a history of recurrent mild painful midline neck swelling, and ultrasound (US) revealed a TGDC that was subsequently managed conservatively. On follow-up after 1.6 years, a thyroid US and a fine-needle aspiration (FNA) biopsy were performed, which showed malignant papillary thyroid carcinoma. Total thyroidectomy, the Sistrunk procedure, and central neck dissection were implemented. After three days, the patient was discharged on 150 mg of levothyroxine. Follow-up was unremarkable with no complications. The authors would like to stress the importance of regular TGDC and thyroid gland follow-ups for early detection and diagnosis of thyroid malignancy via clinical examination and US.